Interactive English Reading Tutor with voice recognition for children / Faizal Rahmat - Rahmat, Faizal (2009)
This project is focus on how to develop an Interactive English Reading Tutor for helping lower primary student to read in English. This topic was chosen because the area of multimodal has a very potential future in the education environment. This project use voice recognition as its multimodal element with storytelling and multimedia approach in it. This will make the Interactive English Reading Tutor efficient, easy to navigate and satisfied the user required. This project deals with unique technical challenges and has been addressed more recently than other domains. Different methods have been proposed and applied to the projects. This paper also provides a comprehensive review of these methods. It will describe background on the field, discussion of the methods and future research directions.